2000
DOI: 10.1007/s004410000202
|View full text |Cite
|
Sign up to set email alerts
|

Increase in NGF content and nerve fiber sprouting in human allergic contact eczema

Abstract: There is increasing evidence for an intimate interaction of the skin and the nervous system. As known from animal studies, nerve growth factor (NGF) is essential for the innervation density and functional properties of sensory neurons of the skin during embryogenesis and in adulthood, and possibly during cutaneous inflammation. This study examined NGF content and sprouting of nerves during the elicitation phase of contact allergy in human skin. Skin biopsies from patients (n=14) undergoing patch-testing were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 44 publications
3
82
1
2
Order By: Relevance
“…Sensitization of itch-signaling pathways has been proposed as a critical mechanism underlying chronic itch (41,42). In ACD and atopic dermatitis, nerve fiber densities are increased in the epidermis (43,44). Extension of these nerve fibers into the epidermis may contribute to spontaneous itch, aggravating itch responses and sensitization of itch signaling pathways (42).…”
Section: Discussionmentioning
confidence: 99%
“…Sensitization of itch-signaling pathways has been proposed as a critical mechanism underlying chronic itch (41,42). In ACD and atopic dermatitis, nerve fiber densities are increased in the epidermis (43,44). Extension of these nerve fibers into the epidermis may contribute to spontaneous itch, aggravating itch responses and sensitization of itch signaling pathways (42).…”
Section: Discussionmentioning
confidence: 99%
“…The rostral back skin was weighed and stored at −80°C until the assay. A summary of the procedure for extracting NGF from the skin was previously given (22). The tissue was homogenized in an extraction buffer containing 0.4 M NaCl, 0.5% bovine serum albumin, 10 mM EDTA (Wako, Osaka), 0.05% Tween (Kanto Kagaku, Tokyo), 20 µL / mL aprotinin, 0.1 mM benzethonium chloride, and 0.1% phenylmethylsulfonylfluoride (Sigma) in phosphate buffer.…”
Section: Methodsmentioning
confidence: 99%
“…First, as noted above, the length of epidermal nerve fibers can be significantly increased in patients with contact eczema 8 or AD, 9 disorders in which mast cells have been implicated. Second, mast cells also are required for optimal expression of certain models of CHS in mice.…”
mentioning
confidence: 93%
“…6 In addition, it has recently been reported that increases in sensory nerve fibers occur in both the epidermis and the dermis in a model of CHS in mice. 7 Moreover, in humans, the length of epidermal nerve fibers can be significantly increased in patients with contact eczema 8 or AD, 9 and increases in both dermal and epidermal nerve fibers have been reported in other dermatological conditions as well, such as prurigo nodularis 10 and notalgia paraesthetica.…”
mentioning
confidence: 97%